Perancangan Sistem Informasi Manajemen Toko Berbasis Web Di Toko Mebel 45 Bojonggede Bogor - Sutanto, Budi; Noris, Shandi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Furniture Store 45 is a business entity engaged in the sale of furniture such as : cabinets, tables, chairs, sofas, tv racks, plate racks, mattresses and others, which located on Jl. Pasar Rebo Kel. Pabuaran Kec. Bojonggede, Bogor. Furniture Store 45 was founded by Mr. Jonatan Sasmita in 2007, assisted by several other employee. The activities that have been carried out at Furniture Store 45 used conventional system The absence of a computerized information system often experiences problems, such as when inputting goods and making sales notes were still handwritten, so it takes a long time to process transactions. It is difficult to find available stock, because employees must have to check the stock in warehouse. Reporting is spend more time and well not structured because it's still recorded in a notebook. The purpose of this research is to build a website-based on store management information system, so that is more simplifying and shortening the time in inputting goods, making sales notes, information on availability of goods, and making reports. Therefore, it is necessary to create a website-based store management information system have been done in the development of this application will be discussed at the end of the thesis.